ANALISIS KESIAPAN INSTANSI DALAM PENERAPAN PAJAK NATURA (STUDI KASUS PADA KABUPATEN BUTON TENGAH) - Marshanda, Ade Linda; Ilham, Surianto; Kartomo, Kartomo (Jurnal Akuntansi Kompetif, 2025)
This study aims to analyze the readiness of government agencies in implementing in-kind taxes in accordance with the Regulation of the Minister of Finance (PMK) Number 66 of 2023 in Central Buton Regency. This study uses a qualitative approach with a case study type. Data sources consist of primary data in the form of interviews with government officials and academics, as well as secondary data from regulations, journals, and official documents. Data analysis was carried out using a descriptive-qualitative method with the stages of data reduction, data presentation, and verification. The results of the study indicate that the readiness of agencies in implementing in-kind taxes is still low. This is due to the lack of socialization from the central government, the absence of clear technical guidelines, and limited human resources and infrastructure that support the implementation of this policy. The efforts that have been made by the relevant agencies are still internal and have not reached the stage of effective implementation. Keywords: